Learning to heal the medical profession in colonial Mexico 1767 - 1831 - Hernández Sáenz, Luz María (Lang, 1997)
The professionalization of medicine in Mexico may be traced back to the eighteenth century when new European ideologies, organization of the Bourbon armies, and changing social values laid its foundations. This work examines the organization of the medical profession, the various branches of medicine, the beginnings of formal surgical education, and the role of women as practitioners. Contemporary treatments are also examined and the quality of medical service compared to that offered in Europe. The analysis of different practitioners and their patients offers a fascinating glimpse of late colonial Mexico while professional rivalry reflects the growing Criollo-peninsular antagonism that would lead to independence.
Keywords: Geschichte 1700-1800; Geschichte 1800-1900; Geschichte 1767-1831; Geschichte 1767-1839; Beroepspraktijk; Enseignement médical - Mexique - Histoire - 18e siècle; Enseignement médical - Mexique - Histoire - 19e siècle; Huisartsen; Médecine - Mexique - Histoire - 18e siècle; Médecine - Mexique - Histoire - 19e siècle; Médecine - Pratique - Mexique - Histoire - 18e siècle; Médecine - Pratique - Mexique - Histoire - 19e siècle; Personnel médical - Mexique - Histoire - 18e siècle; Personnel médical - Mexique - Histoire - 19e siècle; Geschichte; Medizin; Education, Medical -- history -- Mexico; History, 18th Century -- Mexico; History, 19th Century -- Mexico; Medical education -- Mexico -- History -- 18th century; Medical education -- Mexico -- History -- 19th century; Medical personnel -- Mexico -- History -- 18th century; Medical personnel -- Mexico -- History -- 19th century; Medicine -- Practice -- Mexico -- History -- 18th century; Medicine -- Practice -- Mexico -- History -- 19th century; Medicine -- Mexico -- History -- 18th century; Medicine -- Mexico -- History -- 19th century; Sociology, Medical -- history -- Mexico; Gesundheitswesen; Arzt; Professionalisierung; Beruf; Mexiko